Evaluation of Land Capability for Agroforestry Development in Ciliwung Watershed - Rini Fitri (Fakultas Pertanian - UMJ, 2019)
Evaluation of Land Capability for Agroforestry Development in Ciliwung Watershed 1Rini Fitri, 2Nuraida, 3Eka Rahmi1Department of Agrotechnology, Faculty of Agriculture, Almuslim University,2Department of Agroindustrial Technology, Faculty of Agriculture, Almuslim University,3Department of Forestry, Faculty of Agriculture, Almuslim University,Jl. Almuslim Bireuen 24263, Aceh Indonesia*Corresponding author: rinnie_fitrie@yahoo.co.id Abstract Land conversion is one cause of damage to watersheds (DAS), leading to a complex problem physically, economically and socially in the upper and lower watershed. Upper Ciliwung watershed is classified as watershed of which its carrying capacity is restored as it has indicator qualification of high until very high and it is important to be handled. This study was aimed to analyze the cability of upper Ciliwung watershed area for the development of sustainable agroforestry. The units of land use (SPL) used for intensive observation were as many as 60 units of land use spread over seven (7) sub-watershed, namely sub-watershed of Cibalok, Cisuren, Ciliwung, Ciesek, Cisukabirus, Cisarua and Ciseseupan. The unit of land use of which its land capability class was analyzed included the use of shrub land, open land and dry land agriculture. The unit of land use will be used as a recommendation for the use of agroforestry in upper Ciliwung watershed. The results showed that the land capability class in the upper Ciliwung watershed consisted of land capability class II, covering an area of 329.7 ha (23.92%), capability class III of 464.8 ha (33.72%) and capability class IV of 584 ha (42.36%). Land use of upper Ciliwung watershed was dominated by class III with dominant obstacle factor namely bumpy slope. Analysis of land capability on shrubland, open land, and dry land agriculture which spread over the unit of land use in the area of upper Ciliwung watershed was generally recommended for land use of agroforestry-agrisilvopasture and agroforestry-agrisilviculture.Keywords: Land capability, land use, agroforestry, upper Ciliwung Watershed